Cellular Structured CNTs@SiO2 Nanofibrous Aerogels with Vertically Aligned Vessels for Salt‐Resistant Solar Desalination. Issue 34 (19th July 2020) - Dong, Xiangyang; Cao, Leitao; Si, Yang; Ding, Bin; Deng, Hongbing
Abstract: The emerging solar desalination technology is considered as one of the most promising strategies to ensure water security. However, with the proceeding of solar desalination, salt crystallization on the surface of solar evaporators caused by increasing salinity of seawater will result in a decrease in the evaporation rate. Thus, it is still challenging to fabricate solar evaporators with superior salt resistance. In this work, elastic ceramic‐based nanofibrous aerogels with a cellular architecture are fabricated by the combination of electrospinning and fiber freeze‐shaping technologies, which are composed of vertically aligned vessels and porous vessel walls. Under the action of convection and diffusion promoted by this unique cellular architecture, the aerogels exhibit a superior salt‐resistance without any salt crystals on the surface of aerogels even in 20% brine and under 6‐sun irradiation. Moreover, by virtue of the synergistic effect of the promising structure and light absorbance of carbon nanotubes, aerogels possess a high light absorbance of up to 98% and excellent evaporation performance achieving 1.50 kg m −2 h −1 under 1‐sun irradiation. This work may provide a fascinating avenue for the desalination of seawater in a salt‐resistance and efficient manner. Abstract : Salt‐resistant carbon nanotubes@SiO2 nanofibrous aerogels with vertically aligned vessels and porous vessel walls are fabricated for solar desalination. Because of this structure, the aerogels have excellent salt‐resistance without salt crystals on the surface, even in 20% brine and 6‐sun irradiation. Moreover, this material exhibits a light absorbance of 98% and an evaporation rate of 1.50 kg m −2 h −1 under 1‐sun irradiation.